DESIGN OF WEB-BASED ACADEMIC SERVICE SATISFACTION INFORMATION SYSTEM OF WEST SUMATERA SHIPPING POLYTECHNIC - Anggi Minanda Sastra; Nuraeni Dahri; Danyl Mallisza (JENTIK, 2024)
The design of a web-based information system for academic service satisfaction at the West Sumatra Shipping Polytechnic aims to overcome the problems of the survey system which is still manual. This can slow down the process of information at the West Sumatra Shipping Polytechnic. The system design in this Final Project (TA) was built using a website platform and run online. The research method uses the System Development Life Cycle (SDLC) with the Waterfall model approach which consists of 5 stages, namely, a) Analysis b) Design c) Implementation d) Maintenance e) Planing. The programming language used is PHP, and the database application uses the MySql data processor as the database. The system design tool uses the unified Modeling Language (UML) method using 5 (five) diagrams according to design needs, namely Usecase Diagrams, Activity Diagrams, Sequence Diagrams, Class Diagram and database design. This final project produces an effective and efficient Web-based design of an information system for academic service satisfaction at the West Sumatra Shipping Polytechnic that produces accurate and timely survey resultss